PENGARUH AKSES KEUANGAN TERHADAP PERTUMBUHAN UMKM DENGAN MODERASI LITERASI KEUANGAN DI KOTA SEMARANG - Aqida, Merdika Setya; Fitria, Shoimatul (Faculty of Economics and Business Diponegoro University, 2019)
Study about SME’s Growth in Semarang had general purpose to analyze moderating effect of Financial Literacy through the relationship between Financial Access to Finance to SME’s Growth. Financial Literacy to Access to Finance. Others also assesed Financial Literacy and Access to Finance to SME’s Performance in Semarang.This study adopted quantitative research design and used SEM (Structural Equation Model) analysis method by SmartPLS 3.0 to run the data. Population in this research was all UMKM actor in Semarang that put 100 sampel contributing in this research by purposive sampling technique.The finding of the research found Financial Literacy and Access to Finance affect performance, Financial Literacy affects Access to Finance and financial Literacy cannot be mediator for the relationship between Access to Finance to SME’s performance.